Slippery liquid‐infused porous surfaces: The effect of oil on the water repellence of hydrophobic and superhydrophobic soils. (16th October 2020) - McCerery, Rebecca; Woodward, John; McHale, Glen; Winter, Kate; Armstrong, Steven; Orme, Bethany V.
Abstract: Soil wettability is important for understanding a wide range of earth system processes, from agricultural productivity to debris flows and sediment fan formation. However, there is limited research considering how soil–water interactions, where the soil grains are naturally hydrophobic, might change in the presence of oil from natural hydrocarbon leakage or oil spills. Here we show how slippery liquid‐infused porous surfaces (SLIPS) apply to hydrophobic soils, by physical modelling of surfaces of different grain sizes and examining their interactions with water before and after impregnation with silicone oil. Using contact and sliding angle measurements and laser scanning fluorescence confocal microscopy, we demonstrate that soil SLIPS can be created with thick oil layers and thin conformal oil layers on median grain sizes of 231 μ m and 32 μ m, respectively. Until now, SLIPS have only been observed in human‐made materials and biological surfaces. The mechanisms reported here demonstrate that SLIPS can occur in natural granular materials, providing a new mechanism for water‐shedding in soil and sediment systems. Furthermore, the water‐shedding properties may be long lasting as conformal oil layers are stabilized by capillary forces. These results have important implications for understanding soil physics and mechanics where oil is present in a soil, and for agricultural hydrophobicity on shallow slopes. Highlights: We model oil contamination on a hydrophobic model soil as a mechanism for creating SLIPS. Soil SLIPS have implications for water‐shedding, oil spill remediation and earth processes. Our model soils exhibit extreme water‐shedding, illustrated by low water droplet sliding angles. This is the first physical modelling observation of SLIPS arising from hydrophobic soil.